Identification of begomoviruses from different cryptic species of Bemisia tabaci in Bangladesh. (May 2020) - Khatun, Mst Fatema; Hwang, Hwal-Su; Shim, Jae-Kyoung; Kil, Eui-Joon; Lee, Sukchan; Lee, Kyeong-Yeoll
Abstract: Bemisia tabaci is a global species complex consisting of at least 40 cryptic species. It is also a vector for at least 100 species of begomovirus, many of which cause severe crop damage. The relationship between begomoviruses and cryptic species of the B. tabaci species complex, however, remains unclear. Our previous study [13] was identified four cryptic species (Asia I, Asia II 1, Asia II 5, and Asia II 10) of B. tabaci from Bangladesh. Using those 110 whitefly samples, vector-based PCR analysis identified 8 different begomovirus species: BYVMV, BGYVV, OELCV, SLCCV, SLCV, TbCSV, ToLCBV, and ToLCNDV. The overall rate of virus infection was 26.4%, and BYVMV and ToLCNDV were the most frequently detected in the B. tabaci vector. Virus infection rates for Asia I, Asia II 1, Asia II 5, and Asia II 10 were 22.4% (15/67), 35% (7/20), 27.3% (6/22), and 100% (1/1), respectively. Each cryptic species infected multiple virus species, but SLCCV, TbCSV, and BGYVV were each only detected in, Asia I, Asia II 1, and Asia II 5, respectively. This study demonstrates the geographic distribution of various begomoviruses in Bangladesh and their relationships with cryptic species of B. tabaci . Graphical abstract: Image 1 Highlights: Four indigeneous Asian cryptic species of Bemisia tabaci were identified in Bangladesh. Vector-based PCR analysis identified 8 different begomoviruses in Bangladesh. This study provides information of the relationship of cryptic species and begomovirus in Bangladesh .